AN ANALYSIS OF CODE-MIXING USED IN THE HEADLINES OF ECONOMIC-BUSINESS ISSUES IN LOCAL NEWSPAPERS - Lestari, Anggun Riski; Jismulatif, Jismulatif; Dahnilsyah, Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The objectives of this study are to observe what types of code-mixing and the linguistic features of English lexical items of code-mixing used in the headlines of economic-business issues in local newspapers. The study was conducted from March to April 2018 by using mixed method which combines both descriptive qualitative and quantitative method. Findings reports that the most dominant types of code-mixing used are intra-sentential code-mixing (93%) followed by involving a change of pronunciation (5%), and intra-lexical code-mixing (2%). The most dominant the linguistic feature of English lexical items of code-mixing used are proper noun (54.32%) followed by common noun (19.14%), abbreviation (14.20%), adjectives (6.17%), verb (3.09%), prefix (1.85%) and adverb (1.23%).Keyword : Sociolinguistics, Code-Mixing, Headlines